Comparison of Executive Functions and Resilience in Two Groups of Cannabis Users and Non-Users - Ahmadi, Ezzatollah; Chitsaz, Mahdi (Health Nexus, 2024)
The present study aims to compare executive functions and resilience between two groups of cannabis users and non-users. Given the prevalence of cannabis use among young people and its impact on various psychological and social aspects, examining these factors seems essential. This descriptive study is ex-post facto in nature. The statistical population included men and women over 18 years old, from which 60 individuals were selected through convenience sampling. To assess executive functions, the Heppner Problem Solving Inventory and the Carver and White Behavioral Inhibition-Activation Questionnaire were used, and for assessing resilience, the Connor-Davidson Resilience Scale was employed. Data were analyzed using Multivariate Analysis of Variance (MANOVA). The results indicated a significant difference in the behavioral inhibition-activation system between cannabis users and non-users (P<0.05). However, no significant difference was observed in problem-solving and resilience between the two groups. These findings suggest that cannabis use may alter the behavioral inhibition system and the behavioral activation system, while having minimal effect on problem-solving and resilience. Therefore, this research can serve as a basis for further studies on the psychological effects of cannabis use and appropriate intervention strategies to improve the condition of users.